Implementasi Standar Pengelolaan Pendidikan Dalam Meningkatkan Mutu Pendidikan Di SD Negeri 11 Pancung Soal - Shalma Wafiq Azizah; Novriza, Novriza; Azzahra Vidi Umaira; Vebbiola Putri Shasqia; Olvi Sagita (CV. ITTC INDONESIA, 2025)
This article discusses the implementation of Education Management Standards in improving the quality of education at SD Negeri 11 Pancung Soal. Education management standards are a key component of the National Education Standards, which regulate the planning, implementation, supervision, and evaluation of educational activities systematically and sustainably. This study uses a qualitative approach based on literature review to identify strategies, challenges, and the impact of implementing management standards in the elementary school. The findings indicate that SD Negeri 11 Pancung Soal applies self-evaluation-based school planning, structured learning programs, and continuous monitoring and evaluation. The implementation of School-Based Management (SBM) principles provides autonomy to the school in resource management and community involvement. Despite facing challenges such as limited infrastructure and the need for teacher competency development, the school strives to improve education quality through teacher training, facility optimization, and collaboration with various stakeholders. Consistent implementation of management standards has proven to enhance teacher professionalism, accountability, transparency, and the quality of student learning outcomes. These findings suggest that effective implementation of education management standards can be a key factor in improving the quality of education at the elementary level.